IDENTIFIKASI JENIS - JENIS IKAN DI SUNGAI BATANG GADIS KECAMATAN MUARASIPONGI KABUPATEN MANDAILING NATAL SUMATERA UTARA - Anwar anwar; E. Harso Kardhinata; Hanifah Mutia ZNA (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2017)
Research about "Identification the type of fish in Sungai Batang Gadis Muarasipongi subdistrict Mandailing Natal Sumatra Utara" The study aims to determine the types of fish and Chemical Physics parameters. Research using descriptive methods and determination of observation stations is purposive sampling, that the sampling technique. The results of the study there are five types of fish that are grouped into two orders, namely the Cypriniformes and Siluriformes,and 3 Family namely Cyprinidae, Balitoridae, Sisoridae. The conclusion of the study there are 5 types of fish are included in the 2 Order  and 3 Family entirely included into the group Osteichthyes. Most of the Order Cypriniformes and Siluriformes smallest. Most are family Cyprinidae. Results Physical and chemical parameters including water temperature 22oC; pH 7,53; brightness 1.40m; a depth of river 2.28 m; the flow velocity of river 2.09 m / sec; river width of 18 m.